The prevalence of neurological disorders, including those of a palliative nature, in people aged 70 years and over in the Hai district of northern Tanzania. Issue 2 (1st June 2012) - Dewhurst, F.; Dewhurst, M. J.; K. Gray, W.; Howlett, W.; Warren, N.; Orega, G.; Walker, R. W.
Abstract : Introduction: There are few data on neurological disorder prevalence from developing countries, particularly sub-Saharan Africa (SSA), and none specific to the elderly despite a need highlighted by the World Health Organisation. Aims and Methods: We determined the prevalence of neurological disorders in those aged 70 years and over in a rural African community, described their sub-groups including those of a palliative nature, level of diagnosis and treatment and associated disability. We carried out an epidemiological survey in the Hai district demographic surveillance site (DSS) in northern Tanzania (n=161, 119). 2232 participants (1/4 of the DSS 70+ population) were screened with a validated screening questionnaire with high sensitivity (87.8%) and specificity (94.9%). Positive responders underwent full neurological assessment to confirm or refute the presence of a neurological diagnosis. Results: In 2232 participants, there were 384 neurological diagnoses amongst 349 people. The age adjusted prevalence (cases/1000 population) of neurological diagnoses (95% confidence intervals (CI)) was 168.9/1000 (153.4 to 184.5). Palliative neurological disorders included Parkinson's disease, progressive supra-nuclear palsy and motor neuron disease. 14.6% had been correctly diagnosed and 10.6% were on appropriate treatment. Neurological disorders were associated with disability. Conclusion: This is the first community-based neurological disorder prevalence study specifically in the elderly in SSA. It reveals a high prevalence of neurological morbidity, low diagnosis and treatment levels and high associated disability and demonstrates the contribution neurological morbidity makes to the non-communicable disease epidemic.